Indoleamides are active against drug-resistant Mycobacterium tuberculosis - Lun, S.; Guo, H.; Onajole, O.; Pieroni, M.; Gunosewoyo, Hendra; Chen, G.; Tipparaju, S.; Ammerman, N.; Kozikowski, A.; Bishai, W. (Macmillan Publishers Limited, 2013)
Responsible for nearly two million deaths each year, the infectious disease tuberculosis remains a serious global health challenge. The emergence of multidrug- and extensively drug-resistant strains of Mycobacterium tuberculosis confounds control efforts, and new drugs with novel molecular targets are desperately needed. Here we describe lead compounds, the indoleamides, with potent activity against both drug-susceptible and drug-resistant strains of M. tuberculosis by targeting the mycolic acid transporter MmpL3. We identify a single mutation in mmpL3, which confers high resistance to the indoleamide class while remaining susceptible to currently used first- and second-line tuberculosis drugs, indicating a lack of cross-resistance. Importantly, an indoleamide derivative exhibits dose-dependent antimycobacterial activity when orally administered to M. tuberculosis-infected mice. The bioavailability of the indoleamides, combined with their ability to kill tubercle bacilli, indicates great potential for translational developments of this structure class for the treatment of drug-resistant tuberculosis.